Frequency of hyperoxaemia during and after major surgery. Issue 3 (May 2020) - Karalapillai, Dharshi; Weinberg, Laurence; Peyton, Philip J; Ellard, Louise; Hu, Raymond; Pearce, Brett; Tan, Chong; Story, David; O'Donnell, Mark; Hamilton, Patrick; Oughton, Chad; Galtieri, Jonathan; et al.
The oxygen concentration (FiO2 ) and arterial oxygen tension (PaO2 ) delivered in patients undergoing major surgery is poorly understood. We aimed to assess current practice with regard to the delivered FiO2 and the resulting PaO2 in patients undergoing major surgery. We performed a retrospective cohort study in a tertiary hospital. Data were collected prospectively as part of a larger randomised controlled trial but were analysed retrospectively. Patients were included if receiving controlled mandatory ventilation and arterial line monitoring. Anaesthetists determined the FiO2 and the oxygenation saturation (SpO2 ) targets. An arterial blood gas (ABG) was obtained 15–20 minutes after induction of anaesthesia, immediately before the emergence phase of anaesthesia and 15 minutes after arrival in the post-anaesthesia care unit (PACU). We defined hyperoxaemia as a PaO2 of >150 mmHg and included a further threshold of PaO2 >200 mmHg. We studied 373 patients. The median (interquartile range (IQR)) lowest intraoperative FiO2 and SpO2 values were 0.45 (IQR 0.4–0.5) and 97% (IQR 96–98%), respectively, with a median PaO2 on the first and second ABG of 237 mmHg (IQR 171–291 mmHg) and 189 mmHg (IQR 145–239 mmHg), respectively. In the PACU, the median lowest oxygen flow rate was 6 L/min (IQR 3–6 L/min), and the PaO2 was 158 mmHg (IQR 120–192 mmHg). Hyperoxaemia occurred in 82%, 73% and 54% of participants on the first and second intraoperative and postoperative ABGs respectively. A PaO2 of >200 mmHg occurred in 64%, 41% and 21% of these blood gases, respectively. In an Australian tertiary hospital, a liberal approach to FiO2 and PaO2 was most common and resulted in a high incidence of perioperative hyperoxaemia.